Endogenous Plant signals and human Health: Molecular mechanisms, ecological functions, and therapeutic Prospects - Esther Ugo Alum; David Chukwu Obasi; Jacinta Nnennaya Abba; Ugonna Cassandra Aniokete; Prince Nkemakolam Okoroh; Okechukwu Paul-Chima Ugwu; Daniel Ejim Uti (Biochemistry and Biophysics Reports, 2025)
Endogenous plant signals, including phytohormones, secondary metabolites, and volatile organic compounds, play pivotal roles in plant growth, defense, and ecological interactions. Signals are crucial in plant responses to both biotic and abiotic stressors, as well as in the biosynthesis of therapeutic compounds. Jasmonic acid, salicylic acid, and ethylene are crucial signaling molecules that regulate internal and external communication, including herbivore defense and microbial interactions. Volatile organic compounds further enable plant–plant communication and ecological resilience. Increasing evidence links these signaling pathways to the production of compounds with antioxidant, anti-inflammatory, and anticancer properties in humans, bridging plant ecology with human health. This narrative review was conducted through integrative thematic synthesis of peer-reviewed literature published between 2015 and 2025, using databases such as PubMed, Scopus, and ScienceDirect. Articles were selected based on their relevance to the molecular mechanisms, ecological roles, and therapeutic implications of endogenous plant signals. Emphasis was placed on interdisciplinary studies spanning molecular biology, pharmacology, and systems ecology. This review explores recent advancements in plant signals' molecular and ecological roles, emphasizing their importance in sustainable agriculture, drug discovery, and functional foods. Signaling networks' complexity necessitates interdisciplinary strategies involving molecular biology, systems ecology, and pharmacology, which can be harnessed through biotechnology and systems-based research for therapeutic and ecological innovations.